White light emission of wide‐bandgap silicon carbide: A review. Issue 5 (27th January 2022) - Kar, Ajitesh; Kundu, Kusumita; Chattopadhyay, Himadri; Banerjee, Rajat
Abstract: White light‐emitting diodes (LEDs) are the most promising alternative to the conventional lighting sources due to their high efficacy and energy saving in illumination. Silicon carbide (SiC) has a wide optical bandgap and could be tailored to emit light at different wavelengths across the entire visible spectrum by introducing different dopants. Donor and acceptor (DA) co‐doped fluorescent SiC (f‐SiC) is a potential candidate for replacing phosphor material in white LEDs, as it has been observed as a good wavelength converter overcoming the disadvantages of rare earth‐containing phosphors, such as poor color‐rendering index (CRI), short lifetime, and short degradation time. The current study attempts to present an overview on the available approaches to fabricate f‐SiC for generating the white light emission and challenges in fundamental research issues to enhance quantum efficiency, color rendering performance, stability, reproducibility of color quality, and lifetime of f‐SiC.